Isolation Of Nano-Crystalline Cellulose From Waste Cotton Cloths Using Supercritical Carbon Dioxide Technology As Bio Adsorbent For Cr(Vi) Removal - Mohamed, Siti Hajar (2022)
There is an increasing interest in sustainable utilization of waste cotton cloths due to the enormous volume of generation and its high cellulose content. The existing disposal method is open dumping in landfills along with other municipal waste poses environmental pollution and waste of useful resources. Waste cotton cloths contain quality cellulosic materials that can be recycled and reused with the utilization of proper technology. The main objective of this study is to synthesis cellulose nanocrystals (CNCs) from waste cotton cloths for removing Cr(VI) from wastewater. Wherein, the processing of CNCs from waste cotton cloths were conducted using the conventional method (i.e., soda pulping, bleaching and acid hydrolysis) and supercritical carbon dioxide (scCO2) technology.